Responsabilidad social corporativa: qué se hace y qué debe hacerse - Solano, David (2005)
Corporate Social Responsibility has caught the attention of the business community worldwide because consumer and capital markets now champion or punish a company for its relationship with its environment. But this approach is still new and has several defects: it’s reactive, excessively focused on mass media, it’s not specialized, it confuses Public Relations with Social Responsibility, etc. This shows not only little knowledge of the basic concepts but also of the main reason underlying any Social Responsibility process: a sustainable improvement in the relationship with the population as a foundation for sustainable development. In order to achieve this it is necessary to have clear objectives, an clear definition of the target audience, and well designed action plans. Only then will we be able to assess the success or failure of our intervention.